2021
DOI: 10.1111/cts.12959
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetic and exposure‐response analyses of ivosidenib in patients with IDH1‐mutant advanced hematologic malignancies

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Ivosidenib is rapidly absorbed (median time to maximum concentration [ T max ] was typically 2–4 h) and concentrations slowly declined with a mean terminal half‐life ( t ½ ) of ~72–138 h after single dosing and multiple doses in patients with hematologic malignancies. Ivosidenib exhibited an increase in apparent clearance after multiple dose administration which was attributed to a decrease in bioavailability due to auto‐induction of CYP3A4 50 . Ivosidenib is a substrate and an inducer of CYP3A4 and also induces CYP2B6, and CYP2C enzymes.…”
Section: Strong Cyp3a Inducersmentioning
confidence: 99%
See 1 more Smart Citation
“…Ivosidenib is rapidly absorbed (median time to maximum concentration [ T max ] was typically 2–4 h) and concentrations slowly declined with a mean terminal half‐life ( t ½ ) of ~72–138 h after single dosing and multiple doses in patients with hematologic malignancies. Ivosidenib exhibited an increase in apparent clearance after multiple dose administration which was attributed to a decrease in bioavailability due to auto‐induction of CYP3A4 50 . Ivosidenib is a substrate and an inducer of CYP3A4 and also induces CYP2B6, and CYP2C enzymes.…”
Section: Strong Cyp3a Inducersmentioning
confidence: 99%
“…Ivosidenib exhibited an increase in apparent clearance after multiple dose administration which was attributed to a decrease in bioavailability due to auto‐induction of CYP3A4. 50 Ivosidenib is a substrate and an inducer of CYP3A4 and also induces CYP2B6, and CYP2C enzymes. PBPK modeling was used to predict magnitude of CYP2B6, CYP2C8, CYP2C9, and CYP3A4 induction of ivosidenib along with other DDI predictions in patients with cancer.…”
Section: Strong Cyp3a Inducersmentioning
confidence: 99%
“…However, the clinical trials included in our study did not specify dose reductions to account for this interaction, nor is a dose reduction routinely done in our clinical practice. Although we were unable to determine whether a dose reduction of ivosidenib may have resulted in a reduced interaction with triazole antifungals, physiologically based pharmacokinetic studies have shown that ivosidenib exhibits CYP3A4 autoinduction effects at all dose levels of ivosidenib 5,28 . Routine utilization of triazole antifungals and ivosidenib 500 mg daily may not result in an increased rate of observed QTc prolongation partially because of the fact that the serum levels of the azole antifungals are being diminished by ivosidenib itself.…”
Section: Discussionmentioning
confidence: 92%
“…31 However, a population pharmacokinetic analysis observed that increasing area under the curve (AUC) in the presence of azoles was not associated with an increase in clinical toxicity, likely indicating a wide therapeutic window. 32 As a result, the current expert opinion is to exercise “caution” in the presence of azoles and monitor the QTc interval closely while continuing the drug at the full dose of 500 mg per day. 33…”
Section: Isocitrate Dehydrogenase Inhibitorsmentioning
confidence: 99%
“…31 However, a population pharmacokinetic analysis observed that increasing area under the curve (AUC) in the presence of azoles was not associated with an increase in clinical toxicity, likely indicating a wide therapeutic window. 32 As a result, the current expert opinion is to exercise "caution" in the presence of azoles and monitor the QTc interval closely while continuing the drug at the full dose of 500 mg per day. 33 No significant safety concerns were highlighted on using a combination of ivosidenib with azacytidine and venetoclax in a phase Ib/III study, indicating a potentially new combination for IDH1-mutated AML.…”
Section: Ivosidenibmentioning
confidence: 99%